Barbados : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Barbados has a stable political system, and there is long-standing public consensus on key economic policies, including a fixed exchange rate with the U.S. dollar supported by prudent fiscal and wage policies. Owing to job creation mainly in the private sector, particularly construction, the unemployment rate continued to decline, reaching 9.8 percent at the end of 1999, 2 percentage points lower than a year before. The authorities' medium-term strategy aims at stabilizing and restructuring the economy to address ongoing trade liberalization.